Relationship of epitope glycosylation and other properties of blood group proteins to the immunogenicity of blood group antigens. Issue 7 (16th May 2018) - Howe, John G.; Stack, Gary
Abstract : BACKGROUND: The intrinsic properties of polypeptide blood group antigens that determine their relative immunogenicities are unknown. Because size, composition, charge, dose, and epitope glycosylation affect the immunogenicity of other polypeptides, we examined whether similar properties were related to the immunogenicity of blood group antigens. STUDY DESIGN AND METHODS: Amino acid (AA) sequences of antithetical blood group antigens were searched for N‐ and O‐glycosylation sites. Regression analysis was carried out to determine whether blood group protein properties, including total and ectodomain size, red blood cell (RBC) antigen site density, number of mismatched AAs between an antigen and its closest homolog, and differences in mass, charge, and hydrophobicity of the mismatched AAs, were related to immunogenicity. RESULTS: The immunogenicities of non‐RhD polypeptide antigens were directly related to the total and ectodomain sizes of their carrier proteins. A negative power relationship existed between RBC antigen site density and immunogenicity, such that the most immunogenic antigens had the lowest site density. The strong immunogenicity of RhD was related to the number of AA mismatches between RhD and RhCE, to their cumulative hydrophobicity and electrostatic mismatch scores, and the cumulative AA mass difference. No N‐ or O‐glycosylation differences were predicted for antithetical or homologous antigens, other than a previously known N‐glycosylation difference between K and k. CONCLUSION: Epitope glycosylation appeared not to be a determinant of immunogenicity for blood group antigens, except possibly for K. The immunogenicity of blood group antigens was positively related to total and ectodomain sizes of blood group proteins and negatively related to antigen site density. Such findings should be considered hypothesis generating for future, more definitive studies.